2022
DOI: 10.1002/ceat.202100504
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on the Renewable Energy Sector and Mitigation Strategies

Abstract: This review explores the impact of the COVID‐19 pandemic on the renewable energy (RE) sector, especially in countries with the highest RE capacities, e.g., the USA, China, India, and the EU. It highlights stimulus packages put in place by governments worldwide and their sustainability to cushion the RE sector. Commissioning of RE projects has stalled due to lack of funding allocation and interruptions in the supply of equipment and components due to lockdown measures. Despite the need to fund COVID‐19 vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 53 publications
1
25
0
1
Order By: Relevance
“…The study found the instability in consumption at different quantile in selected economic sectors. This difference is not surprising as the economy faces partial lockdown and distance measures carried by the government sporadically (Olabi et al 2022 ; Jiang et al ( 2021 );. Therefore, consumption decreased sharply during and after lifting the lockdown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found the instability in consumption at different quantile in selected economic sectors. This difference is not surprising as the economy faces partial lockdown and distance measures carried by the government sporadically (Olabi et al 2022 ; Jiang et al ( 2021 );. Therefore, consumption decreased sharply during and after lifting the lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Because of restrictions imposed on people’s mobility and activities, significant changes were noticed in renewable and non-renewable energy sources. According to Olabi et al ( 2022 ), renewable energy sources are also significantly influenced by COVID-19, especially wind and solar, which have a considerable share in renewable energy sources. The USA, India, Italy, South Korea, and China experienced a cut down in energy demand and coal output up to 40%, 31%, 20%, 11%, and 9% individually (Brosemer et al 2020 ; Asfour et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Usman and Makhdum [7] argued that "renewable energy consumption could not underestimate to achieve sustainable development goals". Recently, Olabi et al [8] focus on "the investigation of the relationship between renewable energy consumption, economic growth and sustainable development". Razmi et al [9] highlighted that "economic growth rate significantly affects hydroelectric power, wind, solar and biomass energies in developing countries".…”
Section: Introductionmentioning
confidence: 99%
“…These reports have concluded that the outbreak caused serious problems in the renewable energy sector, such as supply chain delays, difficulties in tax stock markets and inability and/or risk for the investors to benefit from government incentives and funds, which were allocated instead towards pandemic relief packages [51,52]. These facts have caused a postponement of many projects and an inevitable drop in the employment of RES energy projects and are further corroborated by several individual papers published after the coronavirus outbreak [53][54][55][56], highlighting the interconnectivity between various sectors and aspects in the modern, globalized economy. Another, equally important factor that inevitably needs to be accounted for with regard to energy transition is no other than the recent energy crisis further exacerbated by the Russian invasion of Ukraine in February of 2022.…”
mentioning
confidence: 98%